A retrospective study of paclitaxel combining nedaplatin chemotherapy for esophageal cancer. Issue 1 (January 2015) - Du, Jianping; Hu, Changlu; Zhang, Yuliu; Hu, Bing; Wang, Fen; Zhang, Yumei
<x xml:space="preserve">Abstract</x> The aim of this study was to evaluate the efficacy and tolerability of the combination of paclitaxel and nedaplatin in patients with advanced esophageal cancer. Patients (n=310) with recurrent or metastatic esophageal squamous cell carcinoma, who had a maximum of one previous chemotherapy regimen, were enrolled in this study. All patients had bidimensionally measurable disease. Patients received 175 mg/m2 of paclitaxel over a 3 h infusion, followed by nedaplatin 80 mg/m2 in a 1 h infusion on day 1 every 3 weeks for up to 6 treatment cycles. The overall response rate was 47.7%, with complete and partial response rates of 6.1 and 41.7%, respectively. The median time to progression for all patients was 6.8 months (95% confidence interval, 6.2–7.4 months) and the 3-year disease-free survival probability was 3 (15.8%). The major toxicity observed was cumulative neutropenia, with 29% patients developing grade 4 toxicity. There was no treatment-related death. The most common nonhematologic toxicity encountered with this regimen was pain and cumulative peripheral neuropathy, with 26% patients experiencing grade 2 or 3 toxicity. The combination of paclitaxel and nedaplatin shows significant antitumor activity and a favorable toxicity profile in patients with metastatic carcinoma of esophageal cancer.